Assessment of endothelial dysfunction in young healthy first-degree relatives with family history of premature coronary artery disease using vascular doppler ultrasonography - Khandait, Vinod; Atkar, Chandrashekhar (International Journal of Research in Medical Sciences, 2019)
Background: Endothelial dysfunction in young healthy first-degree relatives with family history of premature coronary artery disease was assessed in the present study using vascular doppler ultrasonography. Methods: Thirty young (10-40 years) first degree relatives of 17 patients with premature CAD without risk factors were selected for the study. Age and gender matched healthy subjects were enrolled as controls. Non- invasive assessment of endothelial dysfunction was done by vascular doppler study of brachial artery. Brachial artery diameter, velocity and blood flow were estimated in every study subject and control at rest, after stress and again at rest and after glyceryl-trinitrate (GTN) by vascular Doppler ultrasonography. Results: The percent rise in lumen diameter of brachial artery after stress i.e. reactive hyperaemia, labelled as percent rise in flow mediated dilatation (FMD), was significantly lower in family history group than in controls (8.42±3.47% vs 12.22±4.31%, p<0.05). The statistically significant difference in percent rise in FMD was observed to be consistent across different ages/genders (p<0.05). The mean percent rise in FMD among family history group with positive maternal history (8.06±3.65) was lower as compared to those with positive paternal history (8.57±3.12), but the difference was not statistically significant (p>0.05). Conclusions: Apparently healthy young subjects with family history of premature CAD have impaired endothelium dependent FMD in systemic circulation. Simple, non-invasive, cost-effective vascular doppler ultrasonography is recommended as a potential screening tool to detect subclinical atherosclerosis.